Implementação e avaliação de algoritmo de auto-organização para uma arquitetura de rede sem fio baseada em árvore - Sieben, Felipe Groisman (2015)
Improvements in Wireless Sensor Networks (WSNs) are constantly being proposed and one of the challenges is to develop the ability to create smarter dynamics so that it can adapt to the needs that arise in the environment. This work proposes three algorithms for networks based on tree topology: (i) Reorganization of Optimal Power algorithm, (ii) Best Channel Choice Based on ScanED algorithm and (iii) Self-Organizing algorithm, which is the result of the implementation of the first two simultaneously. This last algorithm makes decisions based on metrics such as LQI, RSSI, transmission power, operation channel, CCA and energy detected in channel. The benefits of using this algorithm are: (i) reduction of energy consumption, (ii) reduction of electromagnetic interference in the environment, (iii) achieving a more suitable topology for the needs of the WSN, (iv) reduction of the communication error rate, thus reducing collisions and retransmission of frames, and (v) periodic selection of a clean channel to operate.